The Rich-Club Organization in Rat Functional Brain Network to Balance Between Communication Cost and Efficiency. (20th January 2017) - Liang, Xia; Hsu, Li-Ming; Lu, Hanbing; Sumiyoshi, Akira; He, Yong; Yang, Yihong
Abstract: Network analyses of structural connectivity in the brain have highlighted a set of highly connected hubs that are densely interconnected, forming a "rich-club" substrate in diverse species. Here, we demonstrate the existence of rich-club organization in functional brain networks of rats. Densely interconnected rich-club regions are found to be distributed in multiple brain modules, with the majority located within the putative default mode network. Rich-club members exhibit high wiring cost (as measured by connection distance) and high metabolic running cost (as surrogated by cerebral blood flow), which may have evolved to achieve high network communications to support efficient brain functions. Furthermore, by adopting a forepaw electrical stimulation paradigm, we find that the rich-club organization of the rat functional network remains almost the same as in the resting state, whereas path motif analysis reveals significant differences, suggesting the rat brain reorganizes its topological routes by increasing locally oriented shortcuts but reducing rich-club member-involved paths to conserve metabolic running cost during unimodal stimulation. Together, our results suggest that the neuronal system is organized and dynamically operated in an economic way to balance between cost minimization and topological/functional efficiency.